Correlating serum alpha-fetoprotein in hepatocellular carcinoma with response to Yttrium-90 transarterial radioembolization with glass microspheres (TheraSphere™). Issue 9 (September 2020) - Bhutiani, Neal; O'Brien, Stephen J.; Priddy, Erin E.; Egger, Michael E.; Hong, Young K.; Mercer, Megan K.; McMasters, Kelly M.; Martin, Robert C.G.; Potts, Melissa H.; Scoggins, Charles R.
Abstract: Background: Few studies have assessed the relationship between serum alpha-fetoprotein (AFP) and yttrium-90 (Y-90) radioembolization response in hepatocellular carcinoma (HCC). The objective of the study was to evaluate whether peri-procedural serum AFP was correlated with Y-90 therapy response in HCC. Methods: Patients undergoing Y-90 radioembolization with glass microspheres (TheraSphere™) for HCC between 2006 and 2013 at a single center were evaluated. The relationship between AFP and 6-month radiographic improvement (complete or partial response by modified RECIST criteria), overall (OS), and disease-specific survival (DSS) were analyzed. Results: Seventy-four patients underwent a total of 124 Y-90 infusions. Median age was 65 years, median AFP was 37 ng/mL (range: 2–112, 593 ng/mL) and median model for end-stage liver disease score was 6.2 (range:1.8–11.2). Increased AFP was not associated with radiographic improvement (odds ratio (OR) = 0.99, 95% confidence interval (CI) = 0.75–1.30, p = 0.92). Median OS was 15.2 months and was increased in patients with low AFP compared to high AFP (30.8 months vs. 7.8 months, p < 0.001). On multivariable regression analysis, increased AFP was associated with worse OS (OR = 1.11, 95%CI = 1.01–1.22, p = 0.034) and DSS (OR = 1.13, 95%CI = 1.03–1.25, p = 0.018). Conclusion: Pre-infusion AFP independently predicted survival after Y-90 treatment for HCC, but not radiographic response, and can help guide treatment decisions.